Qualidade microbiológica da água, sedimento e peixe da Laguna da Jansen, São Luís-MA - RODRIGUES JÚNIOR, Luciano de Souza (2019)
The Jansen Lagoon is a coastal lagoon with a typically urban location, situated on the island of São Luís - MA, considered one of the main tourist attractions in the city, much used for fishing activities by the local population. This environment has been impacted negatively due to the disorderly urban growth in its surroundings, as well as being a receiving body of domestic effluents over the years. Therefore, the objective of this study was to evaluate the microbiological quality of water, fish and sediment of the Jansen Lagoon, through the verification of the influence of the physical-chemical parameters of the water on the growth of bacteria, identification of indicator bacteria and multiresistance profile to commercial antibiotics. Were collected 25 samples of water, 15 of sediment and 10 of fish totalling 50 samples.The methodology used to perform the microbiological analyses was the one recommended by the Standard Methods for the Examination of Water and Waste Water of the American Public Health Association to determine the most probable number (MPN) of thermotolerant coliform bacteria and Pseudomonas aeruginosa. The presence of Clostridium perfringens was determined by pour plate inoculation technique using selective agar and anaerobic conditions. Identifications of strains of bacteria isolated were performed through biochemical tests. The physical-chemical parameters of the water were recorded in situ using multi-parameter equipment.The sensitivity profile of strains isolated from commercial antimicrobials was evaluated based on the protocol established by the Clinical and Laboratory Standards Institute. Based on the results obtained, the concentration of soluble solids was directly influenced by the seasonality, especially in the rainy season, where records of the highest values. A similar profile was observed for the population of thermotolerant coliforms that in the rainy season presented the highest counts in the water, in contrast with the sediment, which presented higher indices of contamination in the dry period. In parallel, 130 bacterial strains were isolated and 19 enterobacterial species were identified, with predominance of Escherichia coli in water, sediment and fish samples. Most enterobacteria presented higher resistance to cephalothin (70%), followed by tetracycline (41%).These bacteria were more sensitive to chloramphenicol (91%). The presence of C. perfringens was only detected in the dry period in the water and sediment, not being detected in the fish. In relation to Pseudomonas aeruginosa, the highest fish counts were compared to water and sediment, being strains isolated, susceptible to gentamicin (92.5%) and resistant to sulfazotrim (25%). Based on the data obtained, the rainy season had the highest contamination rates by potentially pathogenic bacteria and was resistant to at least one type of antibiotic. Based on the data obtained, the rainy season presented the highest contamination rates by potentially pathogenic bacteria and multiresistant commercial antibiotics. Therefore, it is necessary to monitor the microbiological quality of these waters in this period as a tool to support decision making in environmental management.